2005
DOI: 10.1192/bjp.187.48.s59
|View full text |Cite
|
Sign up to set email alerts
|

Expressed emotion as an adaptation to loss

Abstract: The results are consistent with Bowlby's attachment theory, where EOI and coercive criticism may be understood as adaptive reactions to perceived loss. Implications for family intervention in first-episode psychosis and the prevention of high EE are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(35 citation statements)
references
References 43 publications
4
31
0
Order By: Relevance
“…The failure to identify significant reductions in levels of EOI may, in part, reflect the complexity of the concept (and measurement) of EOI and difficulties identified within the literature of distinguishing from behaviors and attitudes that can be understood as being caring (van Os et al, 2001; Singh et al, 2013). Early psychosis is characterized by high levels of carer and patient distress and fluctuating symptoms, which may contribute to EE being particularly unstable, changing over time or in relation to stressors rather than intervention (Patterson et al, 2005). Symptom severity or duration were not typically controlled for across the studies, thus limiting the conclusions that can be made in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…The failure to identify significant reductions in levels of EOI may, in part, reflect the complexity of the concept (and measurement) of EOI and difficulties identified within the literature of distinguishing from behaviors and attitudes that can be understood as being caring (van Os et al, 2001; Singh et al, 2013). Early psychosis is characterized by high levels of carer and patient distress and fluctuating symptoms, which may contribute to EE being particularly unstable, changing over time or in relation to stressors rather than intervention (Patterson et al, 2005). Symptom severity or duration were not typically controlled for across the studies, thus limiting the conclusions that can be made in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations into the experience of caring for a relative have revealed that throughout the early stages of psychosis, family members have a significant involvement in a young person’s life; 80–90% of young FEP service consumers reside in the family home [9]. The commencement of acute-phase treatment for psychosis is often overwhelming for families and has been compared to bereavement [10]. During this period family members face the risk of exposure to traumas, such as violence perpetrated by the young person [11, 12], and families worry frequently about behavioural changes [13].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, many carers are negatively affected by their roles, and often report experiencing high levels of ‘burden’ and distress . This is particularly the case in the first episode of psychosis .…”
Section: Introductionmentioning
confidence: 99%